Assessment of nurses’ and assistants’ knowledge on the prevention and management of pressure ulcers - Vrachni, Eleni; Kaba, Evridiki; Fasoi, Georgia; Stavropoulou, Areti; Bourazani, Maria; Kelesi, Martha (Health & Research Journal, 2022)
Background: The pressure ulcers constitute a major clinical problem with enormous socio-economic consequences worldwide. Nurses' knowledge on pressure ulcers’ management plays a crucial role in the prevalence of pressure ulcers. Aim: The investigation of nurses’ knowledge, working in a general hospital, regarding the prevention and management of pressure ulcers. Material and Method: It was a cross-sectional study using a structured questionnaire. The sample consisted of 54 nurses and assistants working in medical and surgical departments of a General Hospital in Athens, Greece. The collection of data took place from June 2019 until November 2019. The analysis of data conducted using the IBM SPSS® program, version 25 (IBM Corp. in Armonk, NY). Results: The mean age of the participants was 42,73 ±8,42 years, and 90,6% were women, with an average work experience of 19,05±9,84 years. The age of nurses of the sample was not associated with the knowledge regarding the prevention of pressure ulcers (p = 0,80). No significant differences were found between their knowledge and the department of work, or the years of work experience and the related seminars organized in the department (p > 0,05). Nurses who had a postgraduate degree had statistically significant more correct answers (p = 0,01). Conclusions: Despite the development of nursing science in the treatment of pressure ulcers, nurses continue to present insufficient knowledge in the daily clinical practice. Τhe implementation of clinical guidelines and the continuing education courses may help nurses to enhance their knowledge.